Respon Pertumbuhan dan Hasil Tanaman Terung (Solanum melongena L.) terhadap Berbagai Dosis Abu Sekam Padi pada Tanah Rawa Lebak - Fenny Erawati (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2012)
Eggplant is one of the vegetables favored by the community. Lebak wetland has the potential for eggplant vegetable cultivation, but the problem with the soil is the physical, chemical and biological properties of the soil that are less favorable. Husk serves to loosen the soil so that it can facilitate plant roots to absorb nutrients. This study aims (i) to determine the growth response and yield of eggplant to various doses of rice husk ash in lebak wetland, (ii) to obtain the best dosage of rice husk ash for growth and yield of eggplant on lebak land. This research was conducted in Hambuku Tengah Village, Sungai Pandan Subdistrict, Hulu Sungai Utara Regency from February - May 2010, this study used a single randomized block design (RBD) with 5 treatments and 4 replications so that 20 experimental units were obtained, each trial unit contained 4 plant. The factor tested was the dose of perpolibag rice husk ash is a0 = 0 or control, a1 = 100 g, a2 = 200 g, a3 = 300 g, and a4 = 400 g. The results showed that giving of rice husk did not affect all variables observed and did not obtain the best dose of dosing treatment for rice husk ash